SIRT1 retention in elongating spermatids interferes with histone displacement by counteracting MOF-dependent H4K16 acetylation - Porreca, Veronica; Chioccarelli, Teresa; Albano, Francesco; Nittoli, Valeria; Ricci, Giulia; Ambrosino, Concetta; Chianese, Rosanna; Mele, Vincenza Grazia; Migliaccio, Antonella; Stornaiuolo, Mariano; Suglia, Antonio; Cobellis, Gilda; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe histone H4 hyperacetylation (i.e., acetylation of H4 at lysines -K5, -K8, -K12, and -K16, here reported as H4tetraAc) occurs in elongating spermatids (eSPTs) during spermiogenesis. Although it is critically involved in histone displacement, the mechanistic involvement of histone -acetyltransferases (HATs) and -deacetylases (HDACs) in the pathway underlying H4 hyperacetylation is poorly defined. Here, we investigate the involvement of SIRT1 deacetylase, and its functional interaction with the histone acetyltransferase MOF, in regulating H4 hyperacetylation underlying histone-to-protamine exchange.MethodsExploiting the cannabinoid receptor 1 (Cb1) null mice (Cb1−/−) as a model of impaired histone displacement, we assessed in eSPTs the expression and the localization of SIRT1 in combination with the enrichment of H4tetraAc and the relative monoacetylated forms (H4-K5ac, -K8ac, -K12ac and -K16ac), by Western Blot and immunohistochemistry analyses. Then, focusing on SIRT1 interaction with MOF HAT by protein immunoprecipitation experiments, we verified the H4K16ac and H4TetraAc enrichment in eSPTs in response to ex vivo SIRT1 inhibition by using the selective EX-527 inhibitor.ResultsWe show that the hyperacetylation of histone H4 occurs progressively in steps 8–9 eSPTs and bursts in step 10 eSPTs, appearing inversely correlated to the expression pattern of SIRT1, being SIRT1 present in step 8, detectable in step 9 and absent in step 10 eSPTs. The abnormal SIRT1 retention in step 10 eSPTs of Cb1−/− mice, despite the observed enrichment of H4-K5ac, -K8ac, and -K12ac, counteracts the H4 hyperacetylation burst by limiting the H4 acetylation at lysine K16. Mechanistically, SIRT1 directly or indirectly interacts with and negatively regulates MOF acetyltransferase, specifically affecting its acetylation status and protein content, thereby interfering with H4K16 acetylation. Counteracting the MOF/SIRT1 interaction by SIRT1 inhibition in ex vivo Cb1−/− testis, both MOF protein content and acetylation status increase, downstream promoting recovery of H4K16ac and H4tetraAc in step 10 eSPT, and full rescue of histone displacement.ConclusionThese results underscore the key involvement of SIRT1–MOF axis in modulating H4K16 acetylation. Our findings provide mechanistic insights into H4K16 acetylation pathway in eSPTs and support the key role of H4K16ac in chromatin remodeling underlying histone displacement.